Management of Diabetes on Long Trips and High Temperatures - Ida Bagus Aditya Nugraha; Ketut Suastika; Wira Gotera; Made Ratna Saraswati; I Made Pande Dwipayana; I Made Siswadi Semadi (Publication Department, Universitas Warmadewa, 2025)
Although safe and fast, air travel can cause problems in diabetic passengers and pilots. In fact, most diabetes-related emergencies can be prevented during the flight. Diabetic passengers and pilots can fly safely with proper control and planning. During air travel, diabetes sufferers are faced with unhealthy diet choices, limited access to medicines and health services, disrupted drug dosing intervals, and exposure to hypobaric aircraft cabin environments. Disruptions to routine dosing intervals are most severe when travelers cross multiple time zones. Traveling east or west will shorten or lengthen the interval between scheduled doses. This increases the possibility of inadvertent, premature, or delayed administration of antihyperglycemic therapy. In this review, we have discussed in detail about flights in diabetic passengers and some issues to be considered during and after the flight especially in high temperature.